Marburg virus evades interferon responses by a mechanism distinct from ebola virus. - Charalampos Valmas; Melanie N Grosch; Michael Schümann; Judith Olejnik; Osvaldo Martinez; Sonja M Best; Verena Krähling; Christopher F Basler; Elke Mühlberger (PLoS Pathogens)
Previous studies have demonstrated that Marburg viruses (MARV) and Ebola viruses (EBOV) inhibit interferon (IFN)-alpha/beta signaling but utilize different mechanisms. EBOV inhibits IFN signaling via its VP24 protein which blocks the nuclear accumulation of tyrosine phosphorylated STAT1. In contrast, MARV infection inhibits IFNalpha/beta induced tyrosine phosphorylation of STAT1 and STAT2. MARV infection is now demonstrated to inhibit not only IFNalpha/beta but also IFNgamma-induced STAT phosphorylation and to inhibit the IFNalpha/beta and IFNgamma-induced tyrosine phosphorylation of upstream Janus (Jak) family kinases. Surprisingly, the MARV matrix protein VP40, not the MARV VP24 protein, has been identified to antagonize Jak and STAT tyrosine phosphorylation, to inhibit IFNalpha/beta or IFNgamma-induced gene expression and to inhibit the induction of an antiviral state by IFNalpha/beta. Global loss of STAT and Jak tyrosine phosphorylation in response to both IFNalpha/beta and IFNgamma is reminiscent of the phenotype seen in Jak1-null cells. Consistent with this model, MARV infection and MARV VP40 expression also inhibit the Jak1-dependent, IL-6-induced tyrosine phosphorylation of STAT1 and STAT3. Finally, expression of MARV VP40 is able to prevent the tyrosine phosphorylation of Jak1, STAT1, STAT2 or STAT3 which occurs following over-expression of the Jak1 kinase. In contrast, MARV VP40 does not detectably inhibit the tyrosine phosphorylation of STAT2 or Tyk2 when Tyk2 is over-expressed. Mutation of the VP40 late domain, essential for efficient VP40 budding, has no detectable impact on inhibition of IFN signaling. This study shows that MARV inhibits IFN signaling by a mechanism different from that employed by the related EBOV. It identifies a novel function for the MARV VP40 protein and suggests that MARV may globally inhibit Jak1-dependent cytokine signaling.